Is housing overvalued in the Helsinki metropolitan area? - Elias Oikarinen (The Research Institute of the Finnish Economy (ETLA), 2005)
This paper studies the housing price dynamics in the Helsinki Metropolitan Area (HMA) using quarterly data from 1975Q1 to 2005Q2. First, the long-run relationship between housing prices and a number of fundamental variables likely to affect the level of housing prices is examined. Several specifications of potential long-run equilibrium relations to which housing prices adjust are estimated. The estimated models are utilized to estimate error-correction and vector error-correction models. Furthermore, the results of the analysis are used to evaluate, whether residential property in the HMA is currently overvalued (or undervalued). The results imply that current housing prices in the HMA correspond to the fundamentals. Based on the econometric analysis, main determinants of the real housing price level are the real lending rate together with current disposable income and income expectations. At present, the biggest fear for a decline in the real housing price level in the HMA comes from the interest rates. The analysis implies that a permanent one percentage-point increase in the real lending rate reduces real housing prices approximately by 4.6% in the long run. The study also shows that the adjustment process of housing prices towards their long-run equilibrium is sluggish, only about 10%-15% per quarter. Furthermore, the response of real housing prices to a shock in the interest rate and income level seems to be cyclical.
Keywords: 330; Housing prices; dynamics; cointegration; error-correction model; bubble; Immobilienpreis; Wohnungsmarkt; Kointegration; Bubbles; Helsinki (Region); Fehlerkorrekturmodell